Field notes contributed by Paul Martsching, fall 1987 - Martsching, Paulet al (1987)
Fall report of birds contributed by Paul Martsching. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed/flatbed